Tackling sustainable development goals through new space - Clegg, S.; Cunha, M. P.; López, A.; Sirage, E.; Rego, J. (Project Leadership and Society, 2024)
Achieving the UN's Sustainable Development Goals (SDGs) constitutes a formidable challenge. Existing solutions may be insufficient to respond to the scale and scope of the endeavour. The 17 SDGs are not discrete but interconnected, sustained by 169 targets. Their cross-level effects require the adoption of a panarchical view of data. New Space projects, still unfamiliar to many managers and organizations, provide such data related to grand challenges capable of addressing the paradoxes that arise from the interaction of a system of systems of multiple scales of spatiality, temporality and social organization. To address these requires project managing developing capabilities that can connect everyday interventions in terrestrial economy and society with high level data findings from Geospatial Information Systems. We contribute to the SDG debate through the articulation of three streams of literature that may radically revise the way wicked problems are addressed: panarchy, paradox, and New Space.